Can Data Complexity Measures Detect Pre-Training Bias in Machine Learning? A Case-Study with Health Data - Leal, Gabriel Difforeni; Rodrigues, Diego Dimer; Silva, Júlia Mombach da; Recamonde-Mendoza, Mariana (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2025)
Bias in healthcare data can negatively impact vulnerable populations and reduce the reliability of predictive models. This work investigates the use of data complexity measures to identify features that may introduce bias during model training with machine learning (ML) algorithms. We analyze a synthetic dataset on schizophrenia and depression and a real dataset on liver disease, evaluating complexity across subgroups defined by protected attributes such as sex and race. The approach is validated against traditional pre-training bias metrics. Preliminary results suggest that data complexity measures can serve as an early indicator of bias, supporting the development of fairer and more transparent predictive models. This framework could inform bias mitigation strategies to improve model fairness in health-related ML applications.